Profile of Bacteria Isolated from the Cell Phones of Health Care Providers in a Hospital Setting in Cameroon - Nguemaïm Ngoufo Flore; Ghangha Jamin Ghangha; Kamga Fouamno Henri Lucien (Bacteria)
Health care providers are an integral part of the era of mobile phones. During various activities linked to health care services, they come in contact with their cell phones regularly. These cell phones act as a perfect substrate for nosocomial pathogens, especially in hot–humid conditions, and may serve as a vehicle in transmitting nosocomial infections. This study aimed at determining the profile of bacteria isolated from the cell phones of healthcare providers. A descriptive cross-sectional study was carried out from 1 April to 3 June 2023, where 115 swab samples were collected from the cell phones of health care providers (laboratory personnel, nurses/midwives and doctors) at the Regional Hospital Bamenda. These swabs were inoculated on blood, chocolate and Mac Conkey plates, and the bacteria were identified according to standard microbiological methods and biochemical tests to the genus/specie level. Data were statistically analyzed using the Statistical Package for Social Sciences (SPSS) version 23. The results were presented in frequencies and proportions. The chi square test was used to compare proportions between variables, and the results were considered statistically significant when p < 0.05. The bacteria isolated from these cell phones included coagulase-negative Staphylococci (CoNS), Staphylococcus aureus, Streptococcus species, Pseudomonas aeroginosa, Escherichia coli, Bacillus species and Neisseria species. All the cell phones of the laboratory personnel were contaminated, followed by those of the nurses/midwives (38; 33.0%) and, lastly, by those of the medical doctors (24; 20.9%). No statistically significant difference was observed between the three categories of health care providers with respect to the presence or absence of bacteria on their cell phones. This study presented that the mobile phones of health care providers are a risk of nosocomial pathogens. The result implies that there is an urgent need to implement and emphasize strategies such as hand washing and decontamination of mobile phones to limit nosocomial infections in the hospital.